LANDASAN PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM UPAYA MEMAJUKAN LEMBAGA PENDIDIKAN ISLAM: Kajian Kurikulum Pendidikan Madrasah dan Pesantren - Syach, Muhammad Alfian; Bariyah, Oyoh; Makbul, M (Universitas Islam Madura, 2024)
The PAI curriculum development model needs serious attention, especially in its application during teaching and learning activities in educational institutions (madrasas and Islamic boarding schools), to develop students' knowledge through IMTAK and science and technology. This research aims to explain the basis for developing a PAI curriculum that is by learning models and development models based on madrasa growth. In this research, the literature study method was carried out to obtain valid and convincing data. The primary data sources used were journals, books, articles, papers, and other relevant sources based on the principles of PAI curriculum development. The analysis used in this research is descriptive data analysis objectively and systematically. Data analysis is methodical and results are taken impartially. The research results show that the curriculum is a system consisting of various components that are interconnected and linked to achieving educational goals. Implementing the Islamic Education curriculum functions as a road map that teachers must follow to direct their students toward the ultimate goal of Islamic education. So the PAI curriculum needs to pay attention to religious components, morals, then cultural aspects, and their utilization. The implications of this curriculum development include: 1) Curriculum renewal, 2) Integration of modern sciences, 3) Development of learning methods, 4) Empowerment of teaching staff, 5) collaboration with stakeholders, 6) Increasing curriculum relevance.